Analysis of Learning Difficulties in Reading and Writing in Class III Students at SDN Batok Bali - Damayanty, Lulu; Rakhman, Patra Aghtiar; Rokmanah, Siti (CV. Rayyan Dwi Bharata, 2023)
This research was motivated by the researcher's observations regarding difficulties in learning to read and write among students in class III which occurred at SDN Batok Bali. This research aims to obtain information or a clear picture of how difficult it is to learn to read and write which is carried out at the SDN Batok Bali school with the learning outcomes achieved by class III students. The research population included all class III students consisting of one class with 41 students. This type of research is qualitative research using a descriptive approach research method, where data collection uses interview, observation and documentation techniques. Based on the results of this research, several difficulties experienced by students were found, including: (a) Difficulty recognizing letters when reading, (b) Difficulty with spelling and unclear reading pronunciation among students, (c) Many errors in reading among students, (d) Difficulty distinguishing several letters when writing, (e) Lack of letters when writing words, (f) The time required to write is too long, and several solutions that can be done to overcome difficulties in learning to read and write in students that have been found in class III at SDN Batok Bali.